2004
DOI: 10.1007/s00595-003-2696-y
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Closure System Type of Nonpenetrating Arcuate-Legged Titanium Clips for Graft-Artery and Graft-Graft Anastomoses: Review of Our Clinical Experience

Abstract: Vascular Closure System clips were useful to coapt a prosthetic graft to an artery unless the arterial wall was thicker than 2 mm or calcified. Thus, VCS clips could be durable enough for graft-artery anastomoses in the iliac or popliteal region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
1
1
0
Order By: Relevance
“…A clinical series examining vascular access in hemodialysis revealed that the application of VCS clips is an easy to manipulate, safe, and time‐saving method compared with hand‐sutured anastomosis . Similar results have been reported for arteriotomy closure after embolectomy, peripheral arterial bypass procedures and graft replacements . Theoretically, the vascular intima is intact, and hyperplasia is absent after achieving anastomosis with non‐penetrating clips, as demonstrated in animal experiments .…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…A clinical series examining vascular access in hemodialysis revealed that the application of VCS clips is an easy to manipulate, safe, and time‐saving method compared with hand‐sutured anastomosis . Similar results have been reported for arteriotomy closure after embolectomy, peripheral arterial bypass procedures and graft replacements . Theoretically, the vascular intima is intact, and hyperplasia is absent after achieving anastomosis with non‐penetrating clips, as demonstrated in animal experiments .…”
Section: Introductionsupporting
confidence: 53%
“…Although positive results were easy to obtain in experimental conditions, the benefit of the VCS was uncertain in patients with atherosclerosis . After performing 100 vascular anastomosis, Yoshinori proposed that if the arterial wall is heavily calcified and thicker than 2 mm, likely due to atherosclerosis, hand sewing with polypropylene should be regarded as the first choice . In our opinion, the complications associated with the VCS were reported in the early phase of its usage and likely occurred at the beginning of the learning curve.…”
Section: Discussionmentioning
confidence: 92%